Decoherence-enabled unconditional strongly sub-Poissonian squeezing - Qing Xu; Ke Zhang; Xiaobo Shen; Haijun Yu; Jiabing Zhu (Physical Review Research)
It is generally accepted that the role of quantum decoherence is to spoil the quantum superpositions and to yield the emergence of the classical behaviors from quantum mechanics. Contrary to the common knowledge of decoherence, we propose a scheme to generate a steady-state bright source of strongly sub-Poissonian squeezed light using the environmentally induced decoherence. The disappearance of the process of decoherence disables the generation of the squeezed state of the combination modes, while the presence of the decoherence results in the strongly nonclassical light source at the sub-shot-noise level and even near-perfect sub-Poissonian squeezed state of light. This excludes the use of the paradigm that the good insulation of a quantum system from its surrounding environment is highly desirable to explore its quantum property and fuel the growth of quantum information science. The interactions with the atom make no contribution to the preparation of squeezed light. These counterintuitive results are originated from the intrinsic quantum reservoir in the dressed-atom combination mode picture, which may open the door to exploring high levels of squeezing induced by the decoherence in the stationary regime.